Does environmental regulation improve residents' health? Evidence from China - Pei, Yunhe; Chen, Hailin; Liu, Zhenhai; Hu, Haozhi (Frontiers in Public Health, 2023)
This paper examines the effect, mechanism, and heterogeneity of environmental regulation affecting residents' health level by using China General Social Survey data. The study found first that environmental regulation has a significant effect on improving the health level of residents. Second, the impact of environmental regulation on residents' health is different among residents with different characteristics. Specifically, the positive impact of environmental regulation on residents' health is stronger among residents with at least a university degree, residents with urban-registered residences, and residents living in economically developed areas. Third, the mechanism analysis found that environmental regulation can improve residents’ health by reducing pollutant emissions and promoting innovation, but it can harm residents’ health by reducing residents’ income. Finally, by introducing a cost–benefit model, it was found that environmental regulation has a significant effect on decreasing economic costs and improving social welfare.